Educação para a saúde: A doença como conteúdo nas aulas de ciências - Oliveira, Silmara Sartoreto [UNESP]; Guerreiro, Lariza Borges; Bonfim, Patrícia Mendes (FapUNIFESP (SciELO), 2007)
The study analyzes how middle-school students view Hansen's disease, which constitutes a public health problem in Brazil. A questionnaire was presented to 159 8th-grade students at three schools, two state and one private. Responses were analyzed by category, with results organized according to knowledge, prejudice about the disease, and the importance of health-education campaigns. The students displayed no scientific knowledge of the disease, although they also showed little prejudice. In terms of educational campaigns, it was concluded that more information of an up-to-date nature should be offered at schools as a way of reaching most of the population.
Health education: Sickness as a subject in science classes
Keywords: Alternative concepts; Brazil; Hansen's disease; Health education